Assessment of the Olea pollen and its major allergen Ole e 1 concentrations in the bioearosol of two biogeographical areas. (November 2016) - Moreno-Grau, S.; Aira, M.J.; Elvira-Rendueles, B.; Fernández-González, M.; Fernández-González, D.; García-Sánchez, A.; Martínez-García, M.J.; Moreno, J.M.; Negral, L.; Vara, A.; Rodríguez-Rajo, F.J.
Abstract: The Olea pollen is currently an important allergy source. In some regions of Southern Spain, olive pollen is the main cause of allergic sensitization exceeding 40% of the sensitized individuals. Due to the scarce presence of olive trees in Northern Spain, limited to some cultivated fields in the South of the Galicia region where they also grow wild, only 8% of the sensitized individuals showed positive results for Olea pollen. The aim of the paper was to assess the behaviour pattern of the Olea pollen and its aeroallergens in the atmosphere, as this information could help us to improve the understanding and prevention of clinical symptoms. Airborne Olea pollen and Ole e 1 allergens were quantified in Cartagena (South-eastern Spain) and Ourense (North-western Spain). A volumetric pollen trap and a Burkard Cyclone sampler were used for pollen and allergen quantification. The Olea flowering took place in April or May in both biometeorological sampling areas. The higher concentrations were registered in the Southern area of Spain, for both pollen and Ole e 1, with values 8 times higher for pollen concentrations and 40 times higher for allergens. An alternate bearing pattern could be observed, characterized by years with high pollen values and low allergen concentrations and vice versa . Moreover, during some flowering seasons the allergen concentrations did not correspond to the atmospheric pollen values. Variations in weather conditions or Long Distance Transport (LDT) processes could explain the discordance. The back trajectory analysis shows that the most important contributions of pollen and allergens in the atmosphere are coincident with air masses passing through potential source areas. The exposure to olive pollen may not be synonym of antigen exposure. Highlights: The highest values in South Spain are for both Ole e 1 and pollen concentrations. Years with high pollen values and low allergen concentrations were registered. The exposure to olive pollen may not be synonym of antigen exposure. LDT processes could explain the discordance between pollen and allergen values.